Improving Employee Work Motivation: Investigating The Mediating Role of Job Satisfaction - Yakup, Yakup; Podungge, Robiyati (Jurnal Ilmiah Sumber Daya Manusia, 2024)
The role of job satisfaction in mediating leadership, organizational support and compensation on employee work motivation. The data used in this research is primary data sourced from filling out questionnaires. The research population was 609 employees of the Regional Public Drinking Water Company in Gorontalo Province. Sampling used the Slovin method to obtain a sample of 145 respondents. The analytical technique used to answer research problems and test hypotheses is path analysis (Path Analisyss) with the help of Statistical Product Service Solution (SPSS) and Lisrel software to analyze the data. The findings of this research are (1) leadership, organizational support, compensation and gender directly have a positive and significant effect on job satisfaction, (2) job satisfaction have a direct positive and significant effect on work motivation, (3) leadership, organizational support, compensation, gender and job satisfaction have a positive and significant direct effect on work motivation, (4) motivation can be increased significantly through the role of job satisfaction on the variables of leadership, organizational support, compensation and gender. Satisfaction is a variable that can change the psychological condition and behavior of individuals regarding the problem of lack of motivation in employees. Job satisfaction can be a lever to increase the drive or enthusiasm of employees to achieve company goals.